The Effect of Third Party Funding and Non Performing Financing on The Development of Islamic Banking Finance in Indonesia - Hasbi Assidiki Mauluddi; Darya Setia Nugraha (Indonesian Journal of Economics and Management, 2022)
This study was performed to determine how much influence of third-party funds and non-performing financing to financing development of Islamic banking in Indonesia. In this study the influence of the amount independent variables partially or simultaneously on the dependent variable. The hypotesis for this research is third-party funds and non-performing financing affects the lending of Islamic banking financing in Indonesia. The data used in this research is secondary data of Bank Indonesia report on the development of Islamic banking. Multiple regression analysis is performed to find the influence of third-party funds and variable non-performing financing the development of financing. The data used in the regression must be pass the classical assumption test. The results of this research note that the third-party funds have a significant effect and non-performing financing no significant effect on the development of Islamic banking financing. Simultaneously, a third-party funds and non-performing financing a significant effect on the development of Islamic banking financing in Indonesia. Both independent variables have contributed as much as 24.7% of the change in the independent variable with a strong enough relationship level by 50%.